Influence of climatic factors on ecological performance of the economy: empirical evidence from BRI countries - Muhammad Rizwanullah; Muhammad Nasrullah; Suliman Almojel (Frontiers in Environmental Science)
Over the past few decades, human activity, particularly CO2 emissions, has been the primary cause of global climate change. Urbanization, population growth, and economic advancements also contribute to increased carbon emissions. Renewable energy projects and green production methods can mitigate CO2 emissions. Despite extensive research on climate change, there is a significant gap in understanding the combined impact of climatic factors such as urban population growth, forest area, electricity production from oil and nuclear sources, and average precipitation on ecological performance in Belt and Road Initiative (BRI) countries. This study aims to fill this gap by analyzing data from 20 BRI countries from 1992 to 2021 using the two-step generalized method of moments (GMM) estimation. The findings reveal that urban population growth and electricity production from oil sources significantly increase CO2 emissions, underscoring the environmental challenges posed by rapid urbanization and fossil fuel dependence. Conversely, forest area and electricity production from nuclear sources demonstrate a mitigating effect, reducing emissions and highlighting the importance of forest conservation and low-carbon energy transitions. Average precipitation depth also shows a significant, though weaker, influence on emissions, highlighting its role in shaping ecological outcomes. This study contributes to the literature by comprehensively assessing climatic factors within the BRI framework by integrating empirical analysis with policy relevance. The results emphasize the need for targeted policies to enhance ecological performance, such as sustainable urban planning, reforestation, and nuclear energy adoption. The research highlights the originality of its methodology and design, offering actionable insights for BRI nations to combat climate change while fostering economic development.